Integrating TQM Practices and Knowledge Management to Enhance Malaysian Digital Banking - Ali Husseini, Saleh; Soo-Fen, Fam (Opción, 2019)
Purpose - The purpose of this study is to develop an integrated model of to- tal quality management (TQM), knowledge management (KM) for Malay- sian digital banking financial crime mitigation to enhance bank reputation. Design/methodology/approach - The quantitative study has been carried out in Malaysian banks. Data were collected from 100 employees the executive management team level and above in banks dyads working in Malaysia and is analyzed through structural equation modeling technique using SPSS 22.0 and SmartPLS 2.0. Findings - The results reveal that Integrating Total Qual- ity Management Practices and Knowledge Management Processes helped in Enhancing Malaysian Digital Banking Reputation, which combat financial crimes through strengthening its anti-money laundering and terror financing capabilities, so as to maintain their global competitive edge in this domain. Re- search limitation/recommendation – the study is only focusing on the digital banking service in Malaysia. There have digital bank where are different with digital banking and also digital banking service in Malaysia might have some different compared to other countries. Hence, there have not standardization of digital banking to be measured. Practical implications – This Findings of study can be utilized by banks to Enhance digital banking reputation, which has been identified as a key to growth and development. Originality/value This study complements the previous researches and seeks to extend literature in digital banking. Malaysia still in earlier stage of adopting digital banking. Hence, reputation can influence decision and confidence of customer.